Direct analysis of tobacco specific nitrosamines in tobacco products using a molecularly imprinted polymer-packed column - Mulder, Haley A.; Poklis, Justin L.; Pearcy, Adam C.; Halquist, Matthew S. (Frontiers in Analytical Science, 2023)
Tobacco specific nitrosamines (TSNAs) are highly carcinogenic by-products in tobacco samples, and their presence is regulated by the Food and Drug Administration. Molecularly imprinted polymers (MIPs) are synthetic polymers that have been “imprinted” with a template analyte in a co-polymer system, and can selectively extract analytes from complex matrices. MIPs can be incorporated into online systems, replacing traditional high performance liquid chromatography (HPLC) columns. MIP material specific for TSNAs was packed into an empty HPLC column using a slurry packing technique. The developed method with the MIP-packed HPLC column was validated on a LC-MS/MS system for the quantitation of N-nitrosonornicotine (NNN) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in commercial tobacco products. The method was linear over 0.1-10 ng/mL (0.4 – 10 g/g) for NNN and NNK. The limit of detection (LOD) was 0.03 ng/mL (.12 g/g) and the limit of quantitation (LOQ), 0.1 ng/mL (0.4 g/g). All column uniformity parameters with the exception of theoretical plate number were within the accepted criteria (%RSD values < 15%). Theoretical plate number was < 250, owing to the large (50 m) sized MIP particles. Twenty-six tobacco products contained TSNA concentrations that were consistent with reported literature values. The TSNA-MIP based HPLC column effectively replaced a traditional reverse phase HPLC column, and was used for the direct analysis of nicotine and tobacco products without extensive sample preparation prior to instrumental analysis.